A SELF-ASSESSMENT MODEL IN TEACHING ACADEMIC WRITING FOR INDONESIAN EFL LEARNERS - Taufiqulloh Taufiqulloh (University of Kuningan, 2014)
Abstract:Â This self-assessment model is developed to help EFL students improve their achievement in academic writing, more particularly essay writing. In English department of Pancasakti University Tegal, academic writing is the course subject which develops models and practices of essay writing in order that students are actively engaged in rhetorical problem-solving. The development of this self-assessment model was derived from the analysis of both theoretical and empirical studies of self-assessment in EFL writing. The self-assessment model developed in this studyÂ consists of four kinds of self-assessment instruments: self-edit checklist of writing dimensions (CWD), checklist of writing strategies (CWS), survey questionnaire of writing interest and awareness (SWIA), and questionnaire of learning monitoring strategies (QLMS). This self-assessment model can be an alternative model in teaching academic writing to EFL students at university level, more particularly the students of English Department, Pancasakti University Tegal.Keywords: self-assessment model, academic writing, Indonesian EFL learners